An Isolated Picochlorum Species for Aquaculture, Food, and Biofuel. (23rd July 2014) - Tran, Duc; Giordano, Mario; Louime, Clifford; Tran, Ngan; Vo, Trung; Nguyen, Du; Hoang, Tung
Abstract: More than 500 marine algal strains in Vietnam were screened for their ability to produce high lipids. Among these, a Picochlorum species of Trebuxiophyceae emerged as the species that had the highest total lipid content with a value of 48.6% dry weight (DW), including 27.84% docosahexaenoic acid (DHA). The remaining lipid was mostly C16 and C18 fatty acids, which is appropriate for biofuel production. In addition, 20 different amino acids were identified and included a high ratio of essential amino acids. Subsequently, the effect of environmental conditions for growth, such as salinity, temperature, and media, on the oleogenic potential of this species was investigated. The alga grew better (μ = 0.25 divisions per day) at a salinity of 0.5 M NaCl in enriched seawater medium (MD1) and at high temperature, but the lipid production was higher at 2 M NaCl in artificial medium (MD2) and at low temperature. Consequently, a two‐phase culture system is recommended for obtaining high nutritional lipids and essential amino acids: MD1 can be used for biomass maximization at a high temperature (25°C), and cells can then be transferred into MD2 at a lower temperature (15°C) for oleogenesis.